Perkampungan Bahasa Arab dalam Mendukung Pembelajaran Mahasiswa di IAIN Parepare - Irwan, Muhammad (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to reveal a description of learning in the Arabic village program implemented by IAIN Parepare as a reinforcement for Arabic learning. As a field research, this study is classified as a qualitative descriptive study under the approach of psycholinguistics, applied psycholinguistics and educational linguistics. The sample is students listed in the Arabic Language Village Program at IAIN Parepare. Data were collected using participatory observation methods, interviews, questionnaires, documentation and reference tracing. The results of this study reveal that the Arabic language village program at IAIN Parepare has a position as an amplifier for Arabic learning that students will face in formal courses at IAIN Parepare. The description of the learning in the program is formulated into learning methods supported by the media and learning objectives. The method used in the Arabic language village program at IAIN Parepare is a combination of several methods that focus on language learning, not language.